2019
DOI: 10.21608/jappmu.2019.64347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biannual Shearing on Body Weight and some Wool Characteristics of Barki Ewes under Semi-Arid Conditions

Abstract: Eighteen adult non-pregnant; non-lactating Barki ewes, aged 3-4 years with initial body weight of 36.71 ± 4.798 (kg) were randomly divided to three groups (n=6). The first group (G1) was kept unshorn along two years (spring 2016 to spring 2018), the second group (G2) was shorn once in the common time of spring (2017) while the third (G3) was shorn biannually in spring and autumn (2017) to investigate the effects of biannual shearing on body weight, some fleece traits, wool production and some wool traits. Mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…El-Gabas (1999) reported values of 0.067 and 0.032 g for GWA and CWA per unit of mid-side position in Barki ewes. Taha (2019) reported that clean wool production of shorn Barki ewes (613g) did not significantly differ from that of control group (555g), representing percentage of 43.04 vs. 37.89%, respectively. Wool gain: The shorn group recorded higher growth rate of net clean wool (5.54g/d) compared to the control group (3.47g/d) as illustrated in Table (3).…”
Section: Growth Performance and Efficiency Of Feed Utilizationmentioning
confidence: 85%
“…El-Gabas (1999) reported values of 0.067 and 0.032 g for GWA and CWA per unit of mid-side position in Barki ewes. Taha (2019) reported that clean wool production of shorn Barki ewes (613g) did not significantly differ from that of control group (555g), representing percentage of 43.04 vs. 37.89%, respectively. Wool gain: The shorn group recorded higher growth rate of net clean wool (5.54g/d) compared to the control group (3.47g/d) as illustrated in Table (3).…”
Section: Growth Performance and Efficiency Of Feed Utilizationmentioning
confidence: 85%